Diabetes may affect the expression of matrix metalloproteinases and their inhibitors more than smoking in chronic periodontitis. (1st July 2016) - Bastos, M. F.; Tucci, M. A.; de Siqueira, A.; de Faveri, M.; Figueiredo, L. C.; Vallim, P. C.; Duarte, P. M.
Abstract : Background and Objective: No previous study has directly compared the levels of matrix metalloproteinases (MMPs) and tissue inhibitor of metalloproteinases (TIMPs) between smokers and individuals with diabetes mellitus (DM) with periodontitis. Therefore, the aim of this study was to evaluate the gene expression of MMP‐1, MMP‐2, MMP‐8, MMP‐9, TIMP‐1 and TIMP‐2 in tissues with chronic periodontitis (ChP) of smokers and individuals with type 2 DM. Material and Methods: Gingival biopsies were harvested from: non‐smokers and non‐diabetic individuals with ChP ( n = 18) (ChP group); non‐diabetic smokers (≥ 10 cigarettes per day for at least the past 5 years) with ChP ( n = 18) (SChP group); non‐smoking individuals with type 2 diabetes (glycated hemoglobin levels ≥ 7.5%) and ChP ( n = 18) (DMChP group). The tissue levels of mRNA of MMP‐1, MMP‐2, MMP‐8, MMP‐9, TIMP‐1 and TIMP‐2 were evaluated by quantitative real‐time polymerase chain reaction. Results: The MMP‐8 expression was the lowest in the ChP group ( p < 0.05). The DMChP group presented increased mRNA levels of MMP‐2 and MMP‐9, when compared to the SChP group ( p < 0.05). MMP‐1 expression and the MMP‐1/TIMP‐1, MMP‐2/TIMP‐1, MMP‐8/TIMP‐1, MMP‐9/TIMP‐1, MMP‐1/TIMP‐2 and MMP‐2/TIMP‐2 ratios were higher in the DMChP group than in the ChP and SChP groups ( p < 0.05). The DMChP group presented lower mRNA levels of TIMP‐1 than the ChP group ( p < 0.05). The MMP‐8/TIMP‐2 ratio was the highest in the SChP group ( p < 0.05). Conclusion: Uncontrolled type 2 DM upregulates the ratio of MMP/TIMPs in sites with ChP more than smoking, which may contribute to a greater extracellular matrix degradation and periodontal breakdown in DM‐related periodontitis.